PENGARUH HUMAN CAPITAL DALAM MENINGKATKAN PENGELOLAAN ZAKAT PADA KANTOR BAZNAS DI PROVINSI SULAWESI BARAT - Yati Heryati; Rahman Rahim; Edi Jusriadi (COMPETITIVENESS, 2021)
This study aims to analyze the competence of human resources, the role of human resources and the performance of human resources of National Amil Zakat Agency (BAZNAS) to improve the management of zakat funds in West Sulawesi Province. This study was conducted at the West Sulawesi Province Baznas Office. This study specifies BAZNAS of West Sulawesi Province as the object of research due to the poor quality of zakat fund management in the BAZNAS office so far. Determination of the subject of research is purposively using qualitative methods. Data for this study was collected through observation and interviews to zakat managers at the BAZNAS Office in West Sulawesi Province. The results of this study indicate that some problems related to the human capital of BAZNAS of West Sulawesi Province. The recruitment process for employee does not uses open-recruitment system, hence the employee hired by BANAS has poor competency and qualification. Collected zakat fund is still focused on zakat of profession, and they have not been able to achieve the maximum target of collection and distribution. This is constrains due to availability of facility and infrastructure. Faced with this problem, BAZNAS of West Sulawesi Province can carry out a more transparent open-recruitment system to open a bigger chance for people who have better competencies to be employed at BAZNAS, start another zakat fund collection program which targets zakat other than zakat of profession, increase employee’s competency with employee training and development program, gives more work motivation, and review governor’s regulation that backed the zakat collection program by adding a sanction to public servants who don’t obey it, as well as expanding the reach of zakat fund distribution and rationalizing the proportion of zakat fund into the predetermined sectors.  Keywords: Human Capital, Performance, Management Zakat.